Serum Endoglin Levels in Patients Suffering from Systemic Sclerosis and Elevated Systolic Pulmonary Arterial Pressure - Garces, Maria Fernanda; Coral-Alvarado, Paola Ximena; Caminos, Jorge Eduardo; Iglesias-Gamarra, Antonio; Restrepo, José Félix; Quintana, Gerardo (International Journal of Rheumatology, 2010)
Background. Pulmonary arterial hypertension (PAH) is the main cause of morbimortality in systemic sclerosis (SSc). Increased Eng expression has been demonstrated in SSc patients. Objective. Ascertaining serum levels of Eng in SSc patients with and without elevated systolic pulmonary arterial pressure (sPAP) and comparing them with that of healthy volunteers. Methods. A cross-sectional study was carried out. A commercial ELISA kit was used for measuring serum concentrations of Eng in 60 subjects: 40 patients with SSc with and without elevated sPAP, compared to 20 healthy control subjects. Elevated sPAP was detected by echocardiogram. Results. No association between positive Eng and elevated sPAP was found when compared to the SSc without elevated sPAP group (OR=2.85; 0.65–12.88 95% CI; P=.11); however, an association was found between positive Eng and elevated sPAP compared to healthy controls (OR=23.22; 2.46–1050.33 95% CI; P=.001), and weak association was found between the positive Eng with SSc without elevated sPAP group compared to healthy controls (OR=8.14, 0.8–393.74 95% CI; P=.046). Conclusion. Raised serum levels of Eng in SSc patients compared to healthy controls were found, suggesting a role for Eng in SSc vasculopathy and not just in elevated sPAP. However, prospective studies are needed to verify such observations.